The Role of Agricultural Extension Workers in Developing Farmer Groups in Rea Village Binuang District Polewali Mandar Regency - Mardawati; Hikmah, Aulia Nurul; Dambe, Jumriani (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Agricultural extension workers are very important to encourage farmers, but their effectiveness in certain areas still needs to be studied in more depth. This study aims to analyze the role of agricultural extension workers in developing farmer groups in Rea Village Binuang District Polewali Mandar Regency. The research method uses primary data obtained through questionnaires from 30 respondents selected by purposive sampling from rice, corn, and cocoa farmer groups. Data analysis uses quantitative descriptive methods and scoring with an ordinal scale to measure the role of extension workers The results of the study showed that the role of agricultural extension workers as motivators, facilitators, organizers, and technicians was in the good category, with a high average score in each aspect. Farmers' assessment of the role of extension workers as motivators with an average score of 2.80 in the good category, farmers' assessment of the role of extension workers as facilitators with an average score of 2.47 was in the good category and farmers' assessment of the role of extension workers as organizers with an average score of 2.47 was in the good category and farmers' assessment of the role of agricultural extension workers as technicians with an average score of 2.50.